2018
DOI: 10.7554/elife.32955
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of ribosomal peptide macrocyclization in plants

Abstract: Constrained, cyclic peptides encoded by plant genes represent a new generation of drug leads. Evolution has repeatedly recruited the Cys-protease asparaginyl endopeptidase (AEP) to perform their head-to-tail ligation. These macrocyclization reactions use the substrates amino terminus instead of water to deacylate, so a peptide bond is formed. How solvent-exposed plant AEPs macrocyclize is poorly understood. Here we present the crystal structure of an active plant AEP from the common sunflower, Helianthus annuu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
137
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(153 citation statements)
references
References 84 publications
8
137
0
8
Order By: Relevance
“…Dissociation of this cap domain occurs upon a shift to a low pH environment where in trans self-cleavage at a flexible linker region occurs. Although previous attempts at producing recombinant butelase 1 failed (Nguyen et al, 2014), by using an E. coli strain optimized for recombinant proteins with disulfide bonds (Lobstein et al, 2012) we found we could successfully express and purify recombinant butelase 1 as we have done for four other plant AEPs (Bernath-Levin et al, 2015;Haywood et al, 2018). The recombinant protein possessed a 6-His tag at its N-terminus, followed by a Gly-Ser linker and 462 residues of butelase 1 from Ile21 to Val482 (Supplemental Figure 1).…”
Section: Crystal Structure Of Butelasementioning
confidence: 71%
See 3 more Smart Citations
“…Dissociation of this cap domain occurs upon a shift to a low pH environment where in trans self-cleavage at a flexible linker region occurs. Although previous attempts at producing recombinant butelase 1 failed (Nguyen et al, 2014), by using an E. coli strain optimized for recombinant proteins with disulfide bonds (Lobstein et al, 2012) we found we could successfully express and purify recombinant butelase 1 as we have done for four other plant AEPs (Bernath-Levin et al, 2015;Haywood et al, 2018). The recombinant protein possessed a 6-His tag at its N-terminus, followed by a Gly-Ser linker and 462 residues of butelase 1 from Ile21 to Val482 (Supplemental Figure 1).…”
Section: Crystal Structure Of Butelasementioning
confidence: 71%
“…Recent structural studies of AEPs have identified subtle amino acid changes around the active site and substrate binding domain that could influence their ability to perform a transpeptidation reaction (Yang et al, 2017;Haywood et al, 2018). The crystal structure of butelase 1 shows that residues surrounding the catalytic His are conserved in asparaginyl endopeptidases (Figure 1C).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the generation of GPI-anchor protein, a C13 protease, GPI-anchor transamidase, mediates the peptide ligation step (Benghezal et al, 1996;Mottram et al, 2003;Bundy et al, 2016). The peptide ligation activity of VPE is required for the formation of toxic cyclic peptides (cyclotides) in plants (Min & Jones, 1994;Saska et al, 2007;Mylne et al, 2011;Nguyen et al, 2014;Bernath-Levin et al, 2015;Yang et al, 2017;Haywood et al, 2018;Jackson et al, 2018); this aspect of VPE function is highlighted below when discussing the important role of VPE in plant defense against insects. In this review, we discuss the functions of VPE during the plant life cycle and summarize the most recent development in the field.…”
Section: Introductionmentioning
confidence: 99%